Design of Tourism-Based Literature Learning - Rully Farida; Dwi Sulistyorini; Dewi Ariani (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study introduces a tourism-based literature learning model to enhance students' motivation, literary appreciation, and cultural literacy in higher education. Traditional literature teaching often lacks engagement and sociocultural context. By integrating cultural and tourism experiences, this model addresses these gaps. Forty undergraduate literature students participated, with data collected through questionnaires, observations, and interviews. Results showed motivation scores increased from 3.05 to 4.25, and participation rose from 37.5% to 75%. Additionally, 82.5% of students reported stronger connections with local culture. Expert validation rated the model highly feasible with a score of 4.4. This approach effectively bridges text and culture, boosting student motivation and engagement, and strengthening cultural literacy.